2018
DOI: 10.21037/jtd.2018.09.108
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory analysis of introducing next-generation sequencing-based method to treatment-naive lung cancer patients

Abstract: Background: The utilization of cancer-linked genetic alterations for categorizing patients against optimal treatment is becoming increasingly popular, especially in non-small cell lung cancer (NSCLC). However, disadvantages of the conventional techniques, such as the low throughput and limited detectable alteration types, lead to the demand of large-scale parallel sequencing for different forms of genetic variants. Methods: We evaluated the potential of performing next-generation sequencing (NGS)-based methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
(38 reference statements)
0
17
0
Order By: Relevance
“… 5 Unfortunately, approximately 40% of patients were still lack of clear driver targets and became a research hotspot currently. 6 Amazingly, the anti-angiogenic drug bevacizumab combined with chemotherapy as first-line treatment achieved superior progression-free survival (PFS) and improved the survival of patients in the BEYOND and ECOG 4599 clinical trial. 7 , 8 Given that the objective response rate (ORR) of first-line platinum-based chemotherapy regimens ranged from 15%-26%, 9 addition of bevacizumab improved the ORR to approximately 50%.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Unfortunately, approximately 40% of patients were still lack of clear driver targets and became a research hotspot currently. 6 Amazingly, the anti-angiogenic drug bevacizumab combined with chemotherapy as first-line treatment achieved superior progression-free survival (PFS) and improved the survival of patients in the BEYOND and ECOG 4599 clinical trial. 7 , 8 Given that the objective response rate (ORR) of first-line platinum-based chemotherapy regimens ranged from 15%-26%, 9 addition of bevacizumab improved the ORR to approximately 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our nomogram did not include other clinical information, including pivotal clinical symptoms, imaging presentations, and comprehensive laboratory indicators such as serum tumor markers [15]. More importantly, accumulating clinical studies revealed the identification of such tumors with alterations in genes such as ALK [21], epidermal growth factor receptor (EGFR) [22][23][24][25], which was momentous to guide tyrosine kinase inhibitors (TKIs) therapy. As an example, approximately 71% of Asiatic patients with PPA harbored EGFR mutation [26] and EGFR-TKIs was used to lengthen progressionfree survival in patients with an EGFR gene mutation and was introduced as first-line therapy in these patients [27].…”
Section: Discussionmentioning
confidence: 99%
“…As an example, approximately 71% of Asiatic patients with PPA harbored EGFR mutation [26] and EGFR-TKIs was used to lengthen progressionfree survival in patients with an EGFR gene mutation and was introduced as first-line therapy in these patients [27]. Moreover, rearrangements of ALK highlighted disease recurrence [23]. With the advent of immune checkpoint inhibitors, PD-L1 protein expression was considered as a well-characterized predictive biomarker for immunotherapy of PPA patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Other smaller DNA-targeted panels have been evaluated on FFPE clinical samples: a good concordance with gold standard methods and a good sensitivity and specificity was observed, the overall amount of DNA input required is usually equal to 50–250 ng [ 47 , 48 , 49 , 50 , 51 , 52 ]. Moreover, this approach has also been specifically tested on critical clinical samples like Endobronchial Ultrasound Guided Transbronchial Needle Aspiration (EBUS).…”
Section: Data Sourcesmentioning
confidence: 99%